DEMOGRAPHIC CHANGES AND ECONOMIC PERFORMANCE IN NIGERIA: AN EMPIRICAL INVESTIGATION - ORJI, Anthony; OGBUABOR, Jonathan E.; NWANOSIKE, Dominic U.; ANTHONY-ORJI, Onyinye I. (Theoretical and Practical Research in Economic Fields; Vol 10 No 1 (2019): TPREF, Volume X, Issue 1(19), Summer 2019, 2019)
Demographic changes in Nigeria are associated with divers’ outcomes. This ranges from unemployment with figures ranging from 14 percent per annum for the entire population to 30 percent for the youth, coupled with stagnating economic performance. Ordinarily the growth of population could be to the advantage of a country in terms of the sheer size of its domestic market, better division of labour, and increased productivity through improvement in the ratio of labour force to population etc but the story may not always be the same for every economy. This study therefore investigated the extent to which demographic changes in Nigeria impact on economic performance in the country, as well as the direction of interaction between population changes and economic performance in Nigeria from 1970-2016. To achieve this, the study adopted Ordinary Least Squares (OLS) and Autoregressive Model (VAR) and found that fertility levels remain moderately high while the death rate drops especially infant mortality, leading to a larger population in Nigeria. Following the research findings, this study recommends that government should enact strict laws prohibiting early sex and marriage among youths. This early engagement on sex and marriage, the paper argued, will increase the mortality rate in Nigeria as a result of sexual infection, unwanted pregnancy as well as reduction in economic performance of the country. Also, serious public enlightenment campaigns should be mounted by government agencies, the mass media, radio, television, chiefs, churches, schools, mosques, home videos, etc. to send across the message that emphasizes the need and importance of family planning, healthy and improved living conditions for the people through population control.